2019
DOI: 10.1021/acs.jpca.9b06769
|View full text |Cite
|
Sign up to set email alerts
|

Dispersion Effects in Stabilizing Organometallic Compounds: Tetra-1-norbornyl Derivatives of the First-Row Transition Metals as Exceptional Examples

Abstract: In 1972 Bower and Tennett first synthesized a series of tetra-1-norbornyl derivatives, (nor) 4 M, of the first-row transition metals from titanium to cobalt. These were found to be exceptionally stable for homoleptic metal alkyls containing only metal−carbon σ-bonds. The theoretical energies for the dissociation of 1-norbornyl ligands from these unusually high oxidation state organometallics through the reactions (nor) 4 M → (nor) 3 M + nor • and (nor) 4 M → (nor) 2 M + nor-nor indicate that dispersion effects… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Dispersion effects are found to be important in structures containing sterically demanding groups. ,, Thus, computational studies have shown that some molecules can be stabilized significantly by dispersion effects. , The B3PW91-D3 method , with Grimme’s D3 dispersion scheme , and the hybrid meta-generalized gradient approximation (GGA) density functional theory (DFT) method ωB97xD functional including empirical dispersion contributions were used with the Gaussian 09 program to optimize the geometries of all structures in the present paper. The reduced density gradients (RDG), indicating the noncovalent weak interactions implemented in Multiwfn were used to study the bonding characters of some selected structures.…”
Section: Theoretical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Dispersion effects are found to be important in structures containing sterically demanding groups. ,, Thus, computational studies have shown that some molecules can be stabilized significantly by dispersion effects. , The B3PW91-D3 method , with Grimme’s D3 dispersion scheme , and the hybrid meta-generalized gradient approximation (GGA) density functional theory (DFT) method ωB97xD functional including empirical dispersion contributions were used with the Gaussian 09 program to optimize the geometries of all structures in the present paper. The reduced density gradients (RDG), indicating the noncovalent weak interactions implemented in Multiwfn were used to study the bonding characters of some selected structures.…”
Section: Theoretical Methodsmentioning
confidence: 99%
“…Iron derivatives in the unusual +4 formal oxidation state are of interest as agents for activating C–H bonds to introduce halogen or oxygenic substituents. , In this regard, many spectroscopic and synthetic studies focus on Fe­(IV) heteroleptic complexes. However, relatively few homoleptic Fe­(IV) species are known and the few such known species have received relatively little attention. The species (cx) 4 Fe (cx = cyclohexyl) , and (nor) 4 Fe (nor = 1-norbornyl) , are two important representative compounds with the four alkyl ligands coordinated to the central Fe­(IV) atom in a nearly ideal tetrahedral environment (Figure ). Dispersion effects have been shown to be significant in stabilizing such species.…”
Section: Introductionmentioning
confidence: 99%
“…The dispersion effect contributes significantly to the stability of the (nor) 4 M (M = Ti to Ni) structures ( Figure 14). [45] However, in the CpM(nor) (M = Ti to Cu) systems, only one norbornyl group is bonded to the central metal atom, limiting the ability of attractive van der Waals interactions to stabilize the CpM(nor) structures. The reduced density gradient (RDG) for (nor) 4 Ni indicates that the Van der Waals interacton plays an essential role in stabilizing the norbornyl transition metals.…”
Section: C1-h1mentioning
confidence: 99%
“…However, in addition to this repulsion, there is growing evidence that attractive London dispersion (LD) interactions between the C–H moieties of the hydrocarbyl substituents of the ligands can generate unexpected effects and enable the formation of species with unusual structures. Such effects are manifested, for example, in the stable hexaphenylethane derivative {C­(C 6 H 3 -3,5- t Bu 2 ) 3 } 2 of Grimme and Schreiner, the divalent group 14 chalcogenetates, high oxidation state mid- to late transition metal alkyls, , or in the low coordinate copper­(II) amides . In pursuit of further examples of low coordinate copper­(II) species, we investigated the use of large terphenyl substituted thiolato ligands where dispersion effects had been noted earlier by Ziegler .…”
Section: Introductionmentioning
confidence: 99%